Risk Factors and Resilience Strategies: Voices From Chinese Novice Foreign Language Teachers - Fan, Lin; Ma, Fang; Liu, Yan-mei; Liu, Tao; Guo, Lin; Wang, Lu-nan (Frontiers in Education, 2021)
In recent years, due to the concern of the high rate of burnout and attrition of teachers in their early career years, teacher resilience has become a vital theme in the study of their professional development. However, little has been done in China. This study contextualized teacher resilience development in Chinese universities and interviewed seven resilient novice foreign language (FL) teachers to explore risk factors confronting them in Chinese contexts and resilience strategies they have employed to cope with these challenges. In-depth interview data and informants’ reflective journals were analyzed inductively by using thematic analysis. The results of the study unfolded risk factors peculiar to Chinese context, and novices’ adoption of resilience strategies was found to involve teachers’ highly selective and dynamic interaction with risk and protective factors, and individual agency manifested itself as an important factor in novice FL teacher resilience development.